Perfil clínico de personalidad mediante el Inventario Clínico Multiaxial (MCMI-II) en población ludópata del Instituto Nacional de Salud Mental Honorio Delgado – Hideyo Noguchi - Paredes Torres, Melissa Noemí (2019)
Objective: Identify and describe the clinical profile of the average personality, determine the percentage of subjectswith personality disorders, determining the existence of severe clinical patterns and pathologies of the personalityand the average iidentificar personality disorders per subject. Methods: The present study was quantitative and descriptive level. The research design was non-experimental, cross-sectional and retrospective. Consisted of 19 patientsdiagnosed with pathological gambling, whose ages ranged between 18 and 60. We used the Spanish adaptation ofthe Millon Clinical Multiaxial Inventory (MCMI-II) Kudo (1999). It took into account only the clinical diseasepatterns and severe pathologies of the personality of MCMI-II. Also analyzed for obtaining a confidence level 0.77for each scale. Results: 79% of the subjects studied had at least one personality disorder. In addition, the scales werepresented more frequently and that scored high were significant: Aggressive-Sadistic (52.6%), narcissistic (42.1%),Passive-Aggressive (42.1%), Avoidant (36, 8%) and Antisocial (36.8%). On the other hand, we obtained an averageof 3.4 personality disorders per subject. Finally, we established the clinical profile of the personality, taking intoaccount the scale with the highest prevalence in the study population. Conclusions: A large percentage of patientswith pathological gambling with comorbid personality disorders